Investigating the Antioxidant and Apoptosis Inducing Effects of Biologically Synthesized Silver Nanoparticles Against Lymphoma Cells in Vitro - Alazzawi, Ahmed Ali; Ghaloub, Abdulameer Naseer; Yaaqoob, Laith Ahmed (Iraqi Journal of Science, 2023)
The current study aimed to synthesize silver nanoparticles (Ag NPs) in a safe and eco-friendly biological method using green tea extract, characterize them using UV-vis spectroscopy, FTIR, XRD, FESEM, and AFM tools, then investigate their antioxidant potentials against DPPH and their cytotoxicity toward lymphoma cells using MTT and ethidium bromide/propidium iodide dual staining assays, and their genotoxic capacities by assessing their effects on the gene expression of p53, caspase3, bcl-2, and bax genes by qPCR and DNA fragmentation.  Results confirmed the synthesis of silver nanoparticles; the UV-vis results showed a peak of absorbance at 414 nm; FTIR analysis showed absorbance belonging to the functional groups of green tea; XRD assay results confirmed the crystallinity of Ag NPs; and AFM revealed a mean diameter of around 24.37 nm. Finally, FESEM showed that the shape of Ag NPs was that of spherical aggregated nanoparticles. The synthesized nanoparticles showed antioxidant activity and cytotoxic effects against lymphoma cells, with an IC50 =  1.138 μg/ml. Cell staining results showed alternations in the shape of treated cells due to apoptosis. Ag NPs affected gene expression as they increased proapoptotic genes p53, caspase3, and bax by 3.3, 2, and 4.25fold, respectively, while decreasing antiapoptotic gene expression bcl-2 by 0.59fold. We concluded that the biological way is an efficient way to synthesize silver nanoparticles, and the synthesized NPs have antioxidant potential and are cytotoxic and genotoxic toward lymphoma cells; thus, they may be utilized in related biomedical applications.